2007
DOI: 10.1021/jm701207m
|View full text |Cite
|
Sign up to set email alerts
|

Amine−Guanidine Switch: A Promising Approach to Improve DNA Binding and Antiproliferative Activities

Abstract: A series of polyaromatic guanidino derivatives was synthesized and evaluated for growth inhibitory properties in several human carcinoma cell lines. The properties of these guanidino compounds were compared to those of their corresponding synthetic amino precursors. The size of the polyaromatic ring system as well as the length of the tether attached to the ring had a direct impact on the observed antiproliferative profiles, compound 14 having the broadest spectrum of activity. As both series intercalate DNA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 44 publications
2
41
0
Order By: Relevance
“…5). This pattern is similar to a previous study (34) showing that a pyrene derivate accumulated in the cytosol of cells. These data suggest that the low level of cytotoxicity observed for these compounds is more likely due to their inability to access nuclear DNA in cells rather than a low binding affinity for DNA, although no studies have been performed to assess the DNA binding affinity of these compounds.…”
Section: Decreasing Viability Of Multiple Mammalian Cell Linessupporting
confidence: 92%
See 1 more Smart Citation
“…5). This pattern is similar to a previous study (34) showing that a pyrene derivate accumulated in the cytosol of cells. These data suggest that the low level of cytotoxicity observed for these compounds is more likely due to their inability to access nuclear DNA in cells rather than a low binding affinity for DNA, although no studies have been performed to assess the DNA binding affinity of these compounds.…”
Section: Decreasing Viability Of Multiple Mammalian Cell Linessupporting
confidence: 92%
“…Previous reports from our group and from other authors have shown that certain derivatives of PAHs, including pyrene and chrysene derivatives, reduce the viability of transformed cell lines (1,20,34), and some of these PAH derivatives have been reported to reduce cell viability by induction of apoptosis (34,35). Therefore, we tested the effects of compounds 1, 2 and 3 on the viability of a small panel of human and mouse cell lines, including liver cancer cell lines (HepG2 and Hepa1-6), colon cancer cell lines (HT-29 and Caco-2), a cervical cancer cell line (HeLa) and NIH3T3 cells.…”
Section: Decreasing Viability Of Multiple Mammalian Cell Linesmentioning
confidence: 72%
“…S9). Although 2 also bound to the protein, it displayed considerably lower affinity (37). These results underscored the importance of both hydrophobic and electrostatic contributions, as well as hydrogen bonding in the protein recognition event.…”
Section: Resultsmentioning
confidence: 82%
“…On the other hand, the critical complexing ratio increases as the content of guanidine group is augmented, manifesting guanidinylated chitosan exhibits a weaker binding strength with DNA compared to chitosan. That is because apart from strong electrostatic interaction, part of guanidine groups may form hydrogen bonding interactions with DNA, 26 and this weaker attraction force inevitably reduces the binding ability of GCS with DNA than amines as reported previously. 16 It is well documented that chitosan becomes soluble and can form polyelectrolyte complexes with polyanions as pH is below its pKa, 6.5.…”
Section: Characterization Of Polyplexesmentioning
confidence: 79%